Metalloporphyrins-Catalyzed Synthesis of 2-Carboxybenzothiazole from 2-Methylbenzothiazole Using Molecular Oxygen as Oxidant - Bai, Jinquan; Hou, Weiwei; Wu, Cuimin; Guo, Ruimei; Xie, Yabo; Li, Jianrong (Current Organocatalysis, 2016)
Background: Heterocyclic compounds containing two or more hetero atoms can represent the most important class of key structural units in a large number of bioactive molecules. Among them, benzothiazole derivatives are often investigated as antitumor, antiviral, and antimicrobial agents, and as important building blocks in pharmaceuticals, agrochemicals and natural products. As one of benzothiazole derivatives, 2-carboxybenzothiazole is an important organic intermediate and taking it as a parent, we can synthesize dipeptide protease inhibitor, it can also be used for the synthesis of anticancer, anti-inflammatory drugs or medicine for treating neural cardiovascular disease. So far, the methods to synthesize 2-carboxybenzothiazole have some defects such as tedious steps, harsh reaction conditions and poor environmental performance. While the biomimetic catalysis of metalloporphyrins (MPs) has increasingly attracted considerable attention, and many processes with the catalysis of metalloporphyrins have been developed. The aims of this paper are to find a simple and green procedure for the synthesis of 2-carboxybenzothiazole from 2-methylbenzothiazole using the metalloporphyrins as biomimetic catalysts and molecular oxygen as oxidant. Methods: 2-Carboxybenzothiazole was prepared according to a typical oxidation procedure: 2-methylbenzothiazole (3.9 mmol), NaOH (0, 0.82, 0.99, 1.31, 1.48, 1.64, 1.8 and 2.05 mol·L;-1), and 10-200 ppm different kinds of metalloporphyrins were dissolved in 30 mL solvent, which were added into a 200 mL autoclave with a magnetic stirrer. Oxygen of 0, 1.0, 1.2, 1.4, 1.6 and 1.8 MPa was inflated into the autoclave. The reaction proceeded for different hours (2, 4, 6, 7, 8, 9, 10 and 12 h) under different temperatures (60, 80, 100, 110, 120, 130 and 140 °C). The reaction liquid was cooled to room temperature, and 5 mol·L-1 of HCl was added to adjust pH value to 5-6. Then the product was obtained and was analyzed by HPLC. Result: The type of solvents, kinds of metalloporphyrins, temperature, reaction time, oxygen pressure, concentration of NaOH and concentration of metalloporphyrin have important influences on the reaction effects. According to a series of experiments, the optimal conditions for the synthesis of 2-carboxybenzothiazole from 2-methyl benzothiazole are as follows: 2-methylbenzothiazole (0.13 mol·L;-1), NaOH (1.64 mol·L;-1), and T(p-OCH3)PPFe (4.1×10;-5 mol·L;-1 ) are placed in a 200 mL autoclave with a magnetic stirrer in 30 mL ethanol, then 1.4 MPa of O2 is inflated into the autoclave and the reaction liquid is heated to 120 °C and keep reaction for 8 hours, the selectivity and conversion can reach 59.1% and 39.2% respectively. Conclusion: A simple and green procedure for the synthesis of 2-carboxybenzothiazole from 2-methylbenzothiazole has been successfully realized by using the metalloporphyrins as biomimetic catalysts and molecular oxygen as oxidant. The catalytic properties of metalloporphyrins and optimum reaction conditions have been explored. Clearly, the central metal ions in the metalloporphyrins have a remarkable effect on their own activities, and metalloporphyrins with Fe2+ as central metal ions have higher catalytic effect than those with Mn2+ and Co2+ as central metal ions. This strategy opens a new opportunity for the preparation of 2-substituted benzothiazole derivatives. Further application of this catalytic system and the amplification experiment are under progress.
Keywords: biomimetic catalysts